The SnRK2.10 kinase mitigates the adverse effects of salinity by protecting photosynthetic machinery. Issue 4 (23rd September 2021) - Mazur, Radosław; Maszkowska, Justyna; Anielska-Mazur, Anna; Garstka, Maciej; Polkowska-Kowalczyk, Lidia; Czajkowska, Anna; Zmienko, Agnieszka; Dobrowolska, Grazyna; Kulik, Anna
Abstract: SNF1-Related protein kinases Type 2 (SnRK2) are plant-specific enzymes widely distributed across the plant kingdom. They are key players controlling abscisic acid (ABA)-dependent and ABA-independent signaling pathways in the plant response to osmotic stress. Here we established that SnRK2.4 and SnRK2.10, ABA-nonactivated kinases, are activated in Arabidopsis thaliana rosettes during the early response to salt stress and contribute to leaf growth retardation under prolonged salinity but act by maintaining different salt-triggered mechanisms. Under salinity, snrk2.10 insertion mutants were impaired in the reconstruction and rearrangement of damaged core and antenna protein complexes in photosystem II (PSII), which led to stronger non-photochemical quenching, lower maximal quantum yield of PSII, and lower adaptation of the photosynthetic apparatus to high light intensity. The observed effects were likely caused by disturbed accumulation and phosphorylation status of the main PSII core and antenna proteins. Finally, we found a higher accumulation of reactive oxygen species (ROS) in the snrk2.10 mutant leaves under a few-day-long exposure to salinity which also could contribute to the stronger damage of the photosynthetic apparatus and cause other deleterious effects affecting plant growth. We found that the snrk2.4 mutant plants did not display substantial changes in photosynthesis. Overall, our results indicate that SnRK2.10 is activated in leaves shortly after plant exposure to salinity and contributes to salt stress tolerance by maintaining efficient photosynthesis and preventing oxidative damage.